Deconstruction of the Ngaben Kusa Pranawa Ceremony in Pujungan Village: A Hindu Theological Perspective - Suadnyana, I Nyoman; Ngurah Sudiana, I Gusti; Alit Putrawan, I Nyoman (MSJ : Majority Science Journal, 2025)
Hinduism demonstrated remarkable dynamism and flexibility, adapting to socio-cultural changes while preserving its core essence. This adaptability manifested in diverse ritual practices, including unique variations of the ngaben (cremation) ceremony in Bali. This study focused on the distinctive ngaben tradition of the Tutuan community in Pujungan Customary Village, Tabanan, which deviated significantly from common Balinese practices. Its uniqueness lay in three key aspects: employing lalang grass as the pengawak (effigy), selecting the officiating priest (pemuput) exclusively from the Brahmana caste (Ida Pedanda), and utilizing specific locations and burial procedures. The research investigated the form, function, and theological meaning of this tradition. It aimed to analyze the relevance of its spiritual, social, and ecological values to contemporary Hinduism and evaluate its resilience to modernization and socio-economic pressures. A descriptive qualitative methodology was employed, integrating ethnographic and Hindu theological approaches. Data were gathered through participatory observation, in-depth interviews, and document analysis, interpreted using deconstruction theory. Results reveal that the Tutuan ngaben transcends mere ancestor veneration. It embodies the principles of tri hita karana (harmony with God, humans, and nature) and tat twam asi (universal self). Lalang grass symbolizes simplicity and ecological connection, while involving Ida Pedanda reflects deep spiritual commitment. Conducting rites at cangkem setra (cemetery edge) with burial demonstrates a contextually faithful interpretation of dharma. The study concludes that this practice represents authentic, contextual, and ecological Hindu spirituality. Preserving it is crucial as intangible Balinese heritage, offering valuable insights for religious, cultural, and spiritual education rooted in local wisdom